Analysis board level that affects on firm performances in real estate property in Indonesia - Yandi Suprapto; Jessica Valeria (Institute of Computer Science (IOCS), 2023)
In this study is to analyze board level that affects on firm performances in real estate property in Indonesia. This study uses board gender, board age, board meetings, board independent and board size as independent variables. For the dependent variables this study uses Firm Performances and also Covid-19 as mediating variable. Research sampling method are the list of real estate property companies in Indonesia whose companies that have included these five independent variables in their companies. Data processed using eviews. The result of the research shows that this independent variable to firm performances didn’t have big impact, but the covid-19 have the impact to these companies